2006
DOI: 10.1089/bar.2006.1.135
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Oral Health Assessment of Bariatric Patients: The Role of the Bariatric Nurse

Abstract: One of the consequences of morbid obesity that has been overlooked is oral health. This paper discusses the oral consequences associated with drugs used to control weight, as well as the oral side effects produced by medications used to treat comorbidities of obesity. We also address how dietary behaviors, and the ergonomic inability to obtain dental care, affect oral health. The relationship between poor oral health and behavior in the bariatric patient are also discussed. Finally, an assessment tool is prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The number of patients presenting with hyposalivation was high, although saliva flow normalized after RYGB. Similarly, another study found that as the BMI increased, the saliva flow decreased, and the researchers explained this finding as a consequence of medication 32 , 33 and the nutrition deficit induced by a diet rich in simple carbohydrates and fat. 11 , 33 …”
Section: Methodsmentioning
confidence: 92%
“…The number of patients presenting with hyposalivation was high, although saliva flow normalized after RYGB. Similarly, another study found that as the BMI increased, the saliva flow decreased, and the researchers explained this finding as a consequence of medication 32 , 33 and the nutrition deficit induced by a diet rich in simple carbohydrates and fat. 11 , 33 …”
Section: Methodsmentioning
confidence: 92%